Effortless cloud-native apps development using Skaffold : simplify the development and deployment of cloud-native spring boot microservices on Kubernetes with Skaffold /: simplify the development and deployment of cloud-native spring boot microservices on Kubernetes with Skaffold. (2021) - Choudhary, Ashish
No abstract available